Vulnerability and resilience in health crises. Evidence from European countries - Dimian, Gina Cristina; Apostu, Simona Andreea; Vasilescu, Maria Denisa; Aceleanu, Mirela Ionela; Jablonsky, Josef (Technological and Economic Development of Economy, 2021)
The purpose of this paper is to draw the first lessons from the on-going coronavirus crisis and to identify viable solutions for what should become the goal of any country: transforming their own economies into sensitive and responsive economies regarding public health problems. The originality of our approach is given by its objective as well as the strategy employed for verifying research hypotheses. The objective is twofold: detecting the indicators that may constitute signals for the vulnerability of countries in times of health crisis and highlighting the underlying factors of the resilience capacity. Many indicators have been considered: six indicators concerning Covid-19 pandemic and 27 socio-economic indicators. Three main hypotheses have been formulated and tested using various statistical methods. Our findings provide deep insights for understanding how Covid-19 crisis is correlated to specific economic (urbanization, sectorial employment, health system) and demographic factors (aging, mortality). The study has succeeded in identifying the pattern of a country with greater resilience and better ability to cope with a health crisis. Our results could be useful when forecasting the spread of another pandemic wave, its impact on people’s health and estimating how some markets will be reshaped.